ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH PERIODE 2013-2016 - Yosi Stefhani (Jurnal Manajemen, 2017)
The purpose of this study is to see whether there is a difference between the financial performance of conventional banks and sharia banks period 2013-2016. Financial performance indicators used in this study are financial ratios of CAR, LDR / FDR, NPL / NPF, BOPO and ROA. In this study the conventional bank samples used are Bank Mandiri, Bank BCA and Bank BNI. Meanwhile, the sharia bank sample in this research is Bank Mandiri Syariah, Bank BCA Syariah and Bank BNI Syariah. Data analysis method used in this research is descriptive analysis and Wilcoxon Signed Ranks test. Based on the results of data analysis and Wilcoxon Signed Ranks test, the result shows that there is no difference of financial performance between conventional bank and syariah bank by using CAR, LDR / FDR and NPL / NPF indicator, but if using BOPO and ROA indicator there is difference between conventional banks and sharia banks. The results also show BOPO and conventional bank ROA better than BOPO and ROA of sharia bank.